Autoantibodies against type I IFNs in patients with life-threatening COVID-19. - Bastard, Paul; Rosen, Lindsey B; Zhang, Qian; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Zhang, Yu; Dorgham, Karim; Philippot, Quentin; Rosain, Jérémie; Béziat, Vivien; Manry, Jeremy; Shaw, Elana; et al. (Science, 2020)
Interindividual clinical variability in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is vast. We report that at least 101 of 987 patients with life-threatening coronavirus disease 2019 (COVID-19) pneumonia had neutralizing immunoglobulin G (IgG) autoantibodies (auto-Abs) against interferon-ω (IFN-ω) (13 patients), against the 13 types of IFN-α (36), or against both (52) at the onset of critical disease; a few also had auto-Abs against the other three type I IFNs. The auto-Abs neutralize the ability of the corresponding type I IFNs to block SARS-CoV-2 infection in vitro. These auto-Abs were not found in 663 individuals with asymptomatic or mild SARS-CoV-2 infection and were present in only 4 of 1227 healthy individuals. Patients with auto-Abs were aged 25 to 87 years and 95 of the 101 were men. A B cell autoimmune phenocopy of inborn errors of type I IFN immunity accounts for life-threatening COVID-19 pneumonia in at least 2.6% of women and 12.5% of men.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Neutralizing; Asymptomatic Infections; Autoantibodies; Betacoronavirus; Case-Control Studies; Coronavirus Infections; COVID-19; Critical Illness; Female; Humans; Immunoglobulin G; Interferon alpha-2; Interferon Type I; Male; Middle Aged; Pandemics; Pneumonia, Viral; SARS-CoV-2

Inborn errors of type I IFN immunity in patients with life-threatening COVID-19. - Zhang, Qian; Bastard, Paul; Liu, Zhiyong; Le Pen, Jérémie; Moncada-Velez, Marcela; Chen, Jie; Ogishi, Masato; Sabli, Ira K D; Hodeib, Stephanie; Korol, Cecilia; Rosain, Jérémie; Bilguvar, Kaya; et al. (Science, 2020)
Clinical outcome upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from silent infection to lethal coronavirus disease 2019 (COVID-19). We have found an enrichment in rare variants predicted to be loss-of-function (LOF) at the 13 human loci known to govern Toll-like receptor 3 (TLR3)- and interferon regulatory factor 7 (IRF7)-dependent type I interferon (IFN) immunity to influenza virus in 659 patients with life-threatening COVID-19 pneumonia relative to 534 subjects with asymptomatic or benign infection. By testing these and other rare variants at these 13 loci, we experimentally defined LOF variants underlying autosomal-recessive or autosomal-dominant deficiencies in 23 patients (3.5%) 17 to 77 years of age. We show that human fibroblasts with mutations affecting this circuit are vulnerable to SARS-CoV-2. Inborn errors of TLR3- and IRF7-dependent type I IFN immunity can underlie life-threatening COVID-19 pneumonia in patients with no prior severe infection.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Asymptomatic Infections; Betacoronavirus; Child; Child, Preschool; Coronavirus Infections; COVID-19; Female; Genetic Loci; Genetic Predisposition to Disease; Humans; Infant; Interferon Regulatory Factor-7; Interferon Type I; Loss of Function Mutation; Male; Middle Aged; Pandemics; Pneumonia, Viral; Receptor, Interferon alpha-beta; SARS-CoV-2; Toll-Like Receptor 3; Young Adult

Type 2 and interferon inflammation regulate SARS-CoV-2 entry factor expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Li, Yingchun; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel C Y; et al. (Nat Commun, 2020)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, an emerging virus that utilizes host proteins ACE2 and TMPRSS2 as entry factors. Understanding the factors affecting the pattern and levels of expression of these genes is important for deeper understanding of SARS-CoV-2 tropism and pathogenesis. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci for both ACE2 and TMPRSS2, that vary in frequency across world populations. We find TMPRSS2 is part of a mucus secretory network, highly upregulated by type 2 (T2) inflammation through the action of interleukin-13, and that the interferon response to respiratory viruses highly upregulates ACE2 expression. IL-13 and virus infection mediated effects on ACE2 expression were also observed at the protein level in the airway epithelium. Finally, we define airway responses to common coronavirus infections in children, finding that these infections generate host responses similar to other viral species, including upregulation of IL6 and ACE2. Our results reveal possible mechanisms influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.
Keywords: Angiotensin-Converting Enzyme 2; Betacoronavirus; Child; Coronavirus Infections; COVID-19; Epithelial Cells; Gene Expression Profiling; Gene Expression Regulation; Genetic Variation; Host-Pathogen Interactions; Humans; Inflammation; Interferons; Interleukin-13; Middle Aged; Nasal Mucosa; Pandemics; Peptidyl-Dipeptidase A; Pneumonia, Viral; SARS-CoV-2; Serine Endopeptidases; Virus Internalization